Synthesis of rigid foam polyurethane from residual palm oil and algae oil for insulated-foam packaging containers - Gomez, Javier Hernando Chavarro (2019)
Future manufacturing technology will drive global growth through innovation in production. Companies are riding on a scale economy to achieve lower costs and keep prices down; thus, keeping ahead of the competition is necessary to remain competitive. In LED Chip on Board (COB) industry, there has been a substantial increase in market demand in recent years, leading to a need for a more costeffective manufacturing process. In Opto-Semiconductor, LED COB products are still produced using batch processing. When product development demand peaks, growth and production are frequently caught unprepared, leading to short-term business losses and long-term deterioration of consumer confidence waiting one year for product. Customers will then flock to the rivals for replacement goods, causing harm to the bottom line of the company. The ultimate objective of this research is to enhance the current LED COB manufacturing process by leveraging surface mount technology (SMT) at the front of the line, saving money, improving the process and improving overall product development cycle time. Based on the research carried out, positive results anticipated from the use of SMT with additional production output of six times more product performance compared to the current output of LED COB, with a capability of printing 960 glue dot in one print, able to maximize COB light-emitting surface (LES) size more than 50mm size and COB board with more panes. These options will help the designer of product development explore new LED COB in the future. This would ensure the competitiveness of production in the future. The Six Sigma method (Define, Measure, Analyze, Improve and Control-DMAIC) with the Design of Experiment (DOE) approach will be used.